Enhanced Cancer Therapy Using an Engineered Designer Cytokine Alone and in Combination With an Immune Checkpoint Inhibitor - Pradhan, Anjan K.; Bhoopathi, Praveen; Maji, Santanu; Kumar, Amit; Guo, Chunqing; Mannangatti, Padmanabhan; Li, Jiong; Wang, Xiang-Yang; Sarkar, Devanand; Emdad, Luni; Das, Swadesh K.; Fisher, Paul B. (Frontiers in Oncology, 2022)
melanoma differentiation associated gene-7 or Interleukin-24 (mda-7, IL-24) displays expansive anti-tumor activity without harming corresponding normal cells/tissues. This anticancer activity has been documented in vitro and in vivo in multiple preclinical animal models, as well as in patients with advanced cancers in a phase I clinical trial. To enhance the therapeutic efficacy of MDA-7 (IL-24), we engineered a designer cytokine (a “Superkine”; IL-24S; referred to as M7S) with enhanced secretion and increased stability to engender improved “bystander” antitumor effects. M7S was engineered in a two-step process by first replacing the endogenous secretory motif with an alternate secretory motif to boost secretion. Among four different signaling peptides, the insulin secretory motif significantly enhanced the secretion of MDA-7 (IL-24) protein and was chosen for M7S. The second modification engineered in M7S was designed to enhance the stability of MDA-7 (IL-24), which was accomplished by replacing lysine at position K122 with arginine. This engineered “M7S Superkine” with increased secretion and stability retained cancer specificity. Compared to parental MDA-7 (IL-24), M7S (IL-24S) was superior in promoting anti-tumor and bystander effects leading to improved outcomes in multiple cancer xenograft models. Additionally, combinatorial therapy using MDA-7 (IL-24) or M7S (IL-24S) with an immune checkpoint inhibitor, anti-PD-L1, dramatically reduced tumor progression in murine B16 melanoma cells. These results portend that M7S (IL-24S) promotes the re-emergence of an immunosuppressive tumor microenvironment, providing a solid rationale for prospective translational applications of this therapeutic designer cytokine.